2015
DOI: 10.1002/sres.2380
|View full text |Cite
|
Sign up to set email alerts
|

Collective Actions in Sustainable Rural Tourism: A Case Study of the Western Region of Paraná

Abstract: This is a study of a collective action oriented to developing rural sustainable tourism in the west of Paraná state, Brazil. We have endeavoured to identify the advantages and disadvantages experienced by rural entrepreneurs while participating in a collective action group. We have carried out a qualitative case study of a descriptive nature, and after interviewing participant entrepreneurs, we concluded that collective action was essential for the development of sustainable rural tourism. Overall, the advanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Therefore, if a destination wants to enhance its capacity for self-determination, it also needs to be aware of the negative aspects of SC (Portes, 2000). For example, when actors with influence, just out of fear of losing their power position, collectively oppose to changes in laws, methodologies or newcomers to participate, limiting heterogeneity in the group, which is a key element for innovation (Schmidt et al, 2016; Williams and Shaw, 2011). An even more negative form of SC also manifests when some actors take unfair advantage of their position and social connections in detriment of fellow participants (Levien, 2015).…”
Section: Sc As the Key Resource For Collective Actions At Tourist Desmentioning
confidence: 99%
“…Therefore, if a destination wants to enhance its capacity for self-determination, it also needs to be aware of the negative aspects of SC (Portes, 2000). For example, when actors with influence, just out of fear of losing their power position, collectively oppose to changes in laws, methodologies or newcomers to participate, limiting heterogeneity in the group, which is a key element for innovation (Schmidt et al, 2016; Williams and Shaw, 2011). An even more negative form of SC also manifests when some actors take unfair advantage of their position and social connections in detriment of fellow participants (Levien, 2015).…”
Section: Sc As the Key Resource For Collective Actions At Tourist Desmentioning
confidence: 99%
“…RHT entrepreneurs see beyond their individual gains to envision the development of the local rural area as an important motivator of value creation (Mottiar, 2016). As such, networks play a major role (Komppula, 2014;Schmidt et al, 2016;Hsu et al, 2013) as this new value creation may come from the constant interaction between actors in a variety of networks, including entrepreneur-entrepreneur (Che et al, 2005;Komppula, 2014;Schmidt et al, 2016;Qu et al, 2020), entrepreneur-tourist (Hsu et al, 2013;Liang, 2017;Yachin, 2019), entrepreneurresearch organizations (Visentin and Vallerani, 2018) and entrepreneur-policymaker networks (Marcouiller and Westeren, 2019). In a new line of research, Schmitz and Lekane Tsobgou (2016) adopted an action research method approach and showed how research on value creation could be a co-evolving process wherein the researcher and the entrepreneurs develop new products ideas together.…”
Section: Innovation and Value Creationmentioning
confidence: 99%
“…Kweon and Lee (2016) mentioned in the study on Daranginon in Gacheon village that while coastal scenery, accessibility, and kindness were their strengths, convenience facilities, visitation costs, meal and beverage prices, purchase of local specialties, hands-on education programs, and various feasts and events were less satisfying. Schmidt et al (2016) stated that collective action is essential for the development of sustainable rural tourism, in which individual or small businesses work together to improve their environments, form associations, syndicates and non-governmental organizations, and achieve common goals.…”
Section: Recognition and Intent-to-participate Of Ure Business Including Tourismmentioning
confidence: 99%